2014
DOI: 10.1111/bjd.13226
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p300 correlates with poor prognosis in patients with cutaneous squamous cell carcinoma

Abstract: Our results indicate that high p300 expression is associated with aggressive features of cSCC and suggest that p300 expression, as examined by IHC, will be a promising biomarker for predicting clinical outcomes in patients with cSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Several reports have demonstrated p300 overexpression in other cancers, including skin, liver, esophageal, nasopharyngeal, lung, breast, prostate and colorectal cancers, and have described the poorer prognoses of patients with tumors with higher p300 expression level than of patients with tumors that express less p300 [916]. However, there is no data regarding p300 expression in pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have demonstrated p300 overexpression in other cancers, including skin, liver, esophageal, nasopharyngeal, lung, breast, prostate and colorectal cancers, and have described the poorer prognoses of patients with tumors with higher p300 expression level than of patients with tumors that express less p300 [916]. However, there is no data regarding p300 expression in pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has suggested an association between p300 overexpression and worse long-term survival of patients with various types of cancer, including lung, liver, colorectal, breast and esophageal cancer [916]. As p300 is involved in diverse biological activities both in benign epithelial and cancerous cells, the mechanism by which the overexpressed p300 impairs treatment outcomes of patients with cancer is not yet clearly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, loss of heterozygosity (LOH) at the p300 locus has been observed in numerous cancers, including hepatocellular, colorectal, oral, breast, ovarian, gastric carcinomas and glioblastomas [11]. Consistently, several studies have also shown that loss of p300 correlates with aggressive features and poor prognosis of hepatocellular carcinoma (HCC) [12, 13], breast cancer [14], cutaneous squamous cell carcinoma (SCC) [15] and nasopharyngeal carcinoma [16]. However, p300 is also found to be overexpressed in prostate cancer, where it regulates fatty acid synthase expression, lipid metabolism and prostate cancer growth [5, 17, 18].…”
Section: Lysine Acetyltransferases Families and Their Link To Cancermentioning
confidence: 99%
“…Overexpression of HATs is observed in a wide variety of cancers. p300 overexpression has been linked to poor prognosis and survival in tumors including breast cancer, non-small cell lung cancer and cutaneous squamous cell carcinoma (Xiao et al, 2011;Hou et al, 2012;Chen et al, 2014). Besides the direct involvement of HATs in the oncogenic fusion, p300/CBP were also shown to modulate the activity of other fusion proteins.…”
Section: Mutations In Histone Acetylating Enzymesmentioning
confidence: 99%